Therapeutic modulation of microbiota-host metabolic interactions - Holmes, Elaine (2013)
The complex metabolic relationships between the host and its microbiota change throughout life and vary extensively between individuals, affecting disease risk factors and therapeutic responses through drug metabolism. Elucidating the biochemical mechanisms underlying this human supraorganism symbiosis is yielding new therapeutic insights to improve human health, treat disease, and potentially modify human disease risk factors. Therapeutic options include targeting drugs to microbial genes or co-regulated host pathways and modifying the gut microbiota through diet, probiotic and prebiotic interventions, bariatric surgery, fecal transplants, or ecological engineering. The age-associated co-development of the host and its microbiota provides a series of windows for therapeutic intervention from early life through old age.